PENGARUH METODE PRAKTIKUM MENGGUNAKAN BAHAN SEHARI-HARI TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA DI SMAN 2 SUNGAI KAKAP PADA MATERI LAJU REAKSI - Wati, Satia; Enawaty, Eny; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to determine the difference in student learning outcomes between students who tought by practicum using everyday materials and conventional methods as well as knowing the influence of practicum methods using everyday materials against learning outcomes eleventh grade student of SMAN 2 Sungai Kakap. Form of research was quasy experimental with Nonequivalent Control Group Design. The technique of sampling was saturated sampling. Data collection technique were observation, measurement techniques and direct communication.. Based on the results of U-Mann Whitney of toward learning after obtained that there is a difference in the activity of students tought by practicum methods using everyday materials and conventional methods with a value Asymp. Sig. (2-tailed) of 0.0004, while the test U-Mann Whitney of toward learning after obtained there is a difference in students learning outcomes that are tought by practicum methods using everyday materials and conventional methods with a value Asymp. Sig. (2-tailed) of 0,012. Based on the calculation of effect size model of the learning method of teaching using everyday materials exert influence of 28,23% against the results of student learning material on reaction rate SMAN 2 Sungai Kakap.Â Keywords: practicum, activities, learning outcomes, reaction rate, everyday materialsÂ